Prevalence of Vitamin B12 Deficiency in Type 2 Diabetes Mellitus Patients on Long-Term Metformin Therapy - Kalyani, Alok Kumar (Journal of Biomedical and Pharmaceutical Research, 2018)
Vitamin B12 deficiency is a common concern in patients with Type 2 diabetes mellitus (T2DM), particularly in those on long-term metformin therapy. Metformin, a first-line drug in the management of T2DM, is known to interfere with vitamin B12 absorption, potentially leading to deficiency. This study aims to determine the prevalence of vitamin B12 deficiency in T2DM patients on long-term metformin therapy and to identify associated risk factors. A total of 150 patients with T2DM on metformin for at least one year were included. Serum vitamin B12 levels were measured, and deficiency was defined as levels below 200 pg/mL. The results showed that 27% of patients had vitamin B12 deficiency, with a higher prevalence in those on metformin for more than five years. Risk factors such as age, duration of metformin use, and BMI were also correlated with deficiency. The study highlights the importance of monitoring vitamin B12 levels in long-term metformin users, particularly in those with additional risk factors. Proactive management and supplementation strategies are necessary to prevent complications associated with B12 deficiency, such as neuropathy and anemia. Keywords: Vitamin B12 deficiency, Type 2 Diabetes Mellitus, metformin, long-term therapy, neuropathy, anemia, risk factors.